Exploring public perceptions of college education on TikTok: A content analysis through the lens of the social determinants of health - Erin Toussaint Jacques; Vincent Jones, II; Erela Datuowei; Arijit Chatterjee; Carlee Denholtz; Corey H. Basch (Dialogues in Health)
This study examines the value of a college degree within the context of the Social Determinants of Health (SDH) framework, analyzing 100 TikTok videos and their respective comments through two separate analyses. The first focused on the video characteristics, including engagement metrics such as likes, comments, shares, and saves, while the second analyzed comment threads for themes within the SDH framework. Data were analyzed using descriptive statistics and the Mann-Whitney U test to evaluate differences in engagement metrics based on the presence or absence of the themes. Videos addressing Employment Opportunities (76 %), Economic Mobility (68 %), and Education Quality (65 %) received the highest engagement. The comment analysis showed significant associations between themes such as Income Potential, Employment Opportunities, Economic Mobility, Social Capital, Debt and Financial Stress with higher video likes. However, health related themes, despite being integral to the SDH framework, were either absent or insignificant in comment discussions. These findings underscore the public's emphasis on financial and career-related concerns over broader health implications. Future research should explore the extent to which SDH-related benefits—such as health resources, access, and literacy—influence decisions about pursuing higher education.